Upaya Peningkatan Rasa Percaya Diri AUD Melalui Kegiatan Bernyanyi Di Depan Kelas - Himatul Munawaroh; Imroatun Imroatun; Busthomi Ibrohim (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2019)
This study aims to improve the confidence of early childhood by using the method of singing in front of the class in group B children at RA Uswatun Hasanah Kec. Kragilan. This research was conducted because of a lack of confidence in the B RA Uswatun Hasanah group. The type of research method used in this activity is Classroom Action Research (CAR) with a research model developed by Kurt Lewin consisting of planning, implementation, observation, and reflection. The location object of Class Action Research at RA Uswatun Hasanah. The results showed that there was an increase in children's confidence that occurred in each Cycle of Cycle 1 and Cycle 2. Where at the 1st Cycle 1 meeting the number of students completed as many as 1 student or 17% of students who had completed, then experienced an increase in completeness at the second meeting as many as 2 students 33% students. In the 2nd cycle of the 1st meeting, there was an increase in completeness of singing activities in the 5th grade students of RA Uswatun Hasanah as many as 5 students or 83%, and at the 2nd meeting all students completed singing or 100% completion. Keywords: efforts, singing activities, self-confidenceReferencesFitriyyah, D. (2016). Membangun Karakter Anak Melalui Dongeng. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 1–10.Huliyah, M. (2016). Pengembangan Daya Seni Pada Anak Usia Dini. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 149–164.Kamtini, & Tanjung, H. W. (2005). Bermain Melalui Gerak dan Lagu di Taman Kanak-Kanak. Jakarta: Departemen Pendidikan Nasional.Nadirah, Y. F. (2016). Mengoptimalkan Otak Anak Sejak Usia Dini. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 186–195.Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-Ilmu Keislaman, 9(1), 49–60.Rasyid, F. (2010). Cerdaskan Anakmu Dengan Musik. Yogyakarta: Diva Press.Setiani, R. E. (2019). Pemanfaatan Permainan Tradisional Dalam Penanaman Nilai-Nilai Kebangsaan Di TK Negeri Pembina 2 Purwokerto. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 4(1), 39–52.Sofiani, T. (2008). Meningkatan Percaya Diri pada siswa Dalam Pembelajaran Matematika Melalui Pendekatan Visual Auditorial Kinestetik. UNS.Susiyati, Mayangsari, D., & Adhani, D. N. (2018). Pengaruh Metode Bernyanyi Terhadap Kemampuan Klasifikasi Benda Pada Anak Kelompok A Di TK Dharma Wanita Blaban Batumar-Mar Pamekasan. JURNAL CARE, 5(2), 14–20.Yamin, M. (2007). Profesionalisme Guru dan Implementasi KTSP. Jakarta: Gaung Persada.Zimmer-Gembeck, M. ., & Collins, W. (2003). Autonomy development during adolescence. In G. R. Adams & M. D. Berzonsky (Eds.), Blackwell handbooks of developmental psychology. Blackwell handbook of adolescence (pp. 175–204). Blackwell Publishing.